What is the role of the board sustainable committee for corporate social responsibility? The moderating effect of gender diversity and ownership concentration - Ahmad Javeed, Sohail; Latief, Rashid; Xiang, Cai; Tze, San Ong; Sun, Qian (Elsevier BV, 2022)
The issue of global warming is becoming more prominent with passage of time, prompting authorities to take action against it. In this context, first, this study focuses on studying the role of the board sustainable committee for corporate social responsibility. Second, this study considers the importance of gender diversity for corporate social responsibility as a moderating factor between board sustainable committee and corporate social responsibility. Third, this study highlights the significance of ownership concentration for improving the corporate social responsibility. Lastly, this study uses the role of ownership concentration as a moderating factor in the association between board sustainable committees and corporate social responsibility. This study uses panel data of 297 Chinese manufacturing firms (2970 observations) for the period 2010–2019, and employs different dynamic panel regression models and robustness test. This study concludes following: first, the board sustainable committee has significance for improving the corporate social responsibility. Second, gender diversity helps to improve the corporate social responsibility. Third, gender diversity helps to enhance the linkage between the board sustainable committee and corporate social responsibility. Fourth, ownership concentration positively affects corporate social responsibility. Fifth, ownership concentration is beneficial to the board sustainable committee and corporate social responsibility. These findings contribute to the literature by providing guidance to the policymakers and regulatory organizations for achieving the sustainable development.